Cover Picture: (Mol. Inf. 1‐2/2017). Issue 1 (January 2017) - Unknown
Abstract : Molecular Informatics publishes research that will deepen our understanding about information storage and processing on the molecular level, signaling and regulation of biological and chemical systems including cellular systems and macromolecular assemblies, modeling of molecular interactions and networks, and the design of molecular modulators that exhibit desired biochemical and pharmacological effects. Various aspects of this transdisciplinary scientific area are depicted on the cover: Cells with their nuclei and membranes (image courtesy of Dr. A. Schreiner and E. Resch), models of receptor‐ligand interactions, and an artistic representation of "biological information" as multiple bit‐codes presented on a right‐handed helix.